Effectieness of junior form pupils’ training of gymnastic exercises in different modes of their fulfillment - Chernenko, S.O. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2015)
Purpose: determination of junior pupils’ motor skills’ formation. Material: in the research 172 pupils participated: in every parallel of forms - 48 pupils. Results: effectiveness of 1 st form pupils’ is positively influenced (exercise - forward roll) by increase of attempts up to 12 times; quantity of repetitions in one attempt shall be within 1-3. For 2 nd form pupils (exercise - forward roll), 3 rd form (exercise - vault over the width of gymnastic horse) and 4 th form pupils (exercise - vault over width of gout with bent legs) positive influence was rendered by increase of repetitions in one attempt up to 3 times and quantity of attempts within 6-12 times. Attention shall be accentuated on quantity of exercise’s repetitions in one attempt (2 nd-4 th forms) and quantity of attempts (4 th from). Conclusions: Experiment of 2 3 type permitted to study multi-factorial structure of modes of 1-4 forms’ schoolchildren’s training to physical exercises; to specify optimal correlations of quantity of attempts, quantity of repetitions in one attempt and rest interval in period of acrobatic exercises’ and gymnastic vaults’ training at physical culture lessons.